Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Terhadap Kinerja Pegawai Pada Badan Pengelolaa Keuangan dan Pendapatan Daerah Kabupaten Pamekasan Yang Di Mediasi Oleh Motivasi - Selly Furima; Subijanto Subijanto; Mei Indrawati (Universitas 45 Surabaya, 2024)
Selly Furima, 2024. The Effect of HR Competencies and Career Development on the Quality of Public Services Mediated by Employee Performance (Study at the Office of the Regional Revenue Agency Kab. Kaimana), Postgraduate Program, Wijaya Putra University. This type of research is explanatory, namely research that tests hypotheses between hypothesized variables that will be tested for truth. using a quantitative approach, the research sample was 40 respondents. In this study the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To describe HR competencies, career development, employee performance and public service quality. 2) To test and analyze the direct effect of HR competencies on the quality of public services. 3) To test and analyze the direct effect of HR competencies on employee performance. 4) To test and analyze the direct effect of career development on the quality of public services. 5) To test and analyze the direct effect of career development on employee performance. 6) To test and analyze the direct effect of employee performance on the quality of public services. 7) To test and analyze the indirect effect of HR competencies on the quality of public services. 8) To test and analyze the indirect effect of career development on the quality of public services.The results showed that: 1) HR competence has a positive and significant effect on the quality of public services. This is evidenced by the original sample value of 0.223 and p-values of 0.000. 2) HR competence has a positive and insignificant effect on employee performance. This is evidenced by the original sample value of 0.597, and the p-values of 0.179. 3) Career development has a positive and insignificant effect on the quality of public services. This is evidenced by the original sample value of 0.198 and the p-values of 0.263. 4) Career development has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.279 and the p-values of 0.025. 5) Employee performance has a positive and significant effect on the quality of public services. This is evidenced by the original sample value of 0.512 and the p-values of 0.000. 6) HR competence has a significant positive effect on the quality of public services mediated by employee performance. This is evidenced by the original sample value of 0.305 and the p-values of 0.009. 7) Career development has a significant positive effect on the quality of public services mediated by employee performance. This is evidenced by the original sample value of 0.143 and the p-values of 0.038.